(untitled) (Journal of history-rus, 2021)
Afghanistan is on the path of the history by Mir Ghulam Mohammad Ghobar. This book is a mas- terpiece in its own time that has been written as a documentary analysis. This is the first book in the country that was banned by the government after it was published for eleven years. This made the author and his book famous. This book is written in a scientific style, with Shiva literature and documentary analytical method. However, in terms of writing style and literature, there are differences between the first and second volumes. The contents of this book are the history of Afghanistan which covers the dis- tant past to the end of Mohammad Zahir Shah’s time. According to the author, the contents of the book are the political history of Afghanistan, not its social history. The author believes that political history can be written separately from the history of neighbors. For this reason, there are a few shortcomings in the study of historical periods in this book. The author has tried to reconcile the past with the political boundaries of today. Therefore, it cannot consider a specific criterion for recognizing past governments. He called the governments of Afghans whose only ancestors were from present-day Afghanistan. It does not consider governments to be Afghans who are both of current Afghan descent and have ruled Afghani- stan. The text of the book is decorated with interesting and beautiful analysis. Historical facts are rippling through it. However, I see some shortcomings and undocumented analyzes in it that cannot damage the reputation of the book. The sources used in the book are primary sources. The way of writing the sources has not been treated in the same way. Ghobar sources are not only Persian or Pashto works but also Arabic, Russian and English books as sources. It seems that the style and method of Afghanistan’s writing in the course of history are influenced by the method of the historian Leopold von Range, who has a German-style. Key words: Afghanistan in the path of history, Ghobar, critique, writing method.